2011
DOI: 10.1510/icvts.2010.259747
|View full text |Cite
|
Sign up to set email alerts
|

Combined anti-calcification treatment of bovine pericardium with amino compounds and solvents

Abstract: The objective of this study was to evaluate the effect of treatment with amino compounds and solvents in vivo on calcifications of glutaraldehyde (GA)-fixed pericardium. Groups of bovine pericardium samples were fixed with 0.5% GA. We used urazole and glutamate to neutralize the free aldehyde and some solvents (ethanol with octanol or octanediol) to reduce the phospholipid content in the bovine pericardial tissue. Tensile strength and thermal stability were evaluated before implantation. Twelve weeks after rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…Previously, we proved the efficacy of our combined anti-calcification treatments for GA-fixed cardiac xenografts in small-animal experiments [6,8,9]. However, these anti-calcification treatments have not always been safe and efficacious if used on valves placed under in vitro mock circulation or large-animal in vivo circulation [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we proved the efficacy of our combined anti-calcification treatments for GA-fixed cardiac xenografts in small-animal experiments [6,8,9]. However, these anti-calcification treatments have not always been safe and efficacious if used on valves placed under in vitro mock circulation or large-animal in vivo circulation [2].…”
Section: Discussionmentioning
confidence: 99%
“…Our treatment targeted at the prevention of calcification includes the extraction of phospholipids [6,8,9], neutralization of residual unbound aldehyde groups of GA [6,8,9], and decellularization [6,10,11]. We also developed a specially designed mold for the manufacture of the valved conduit [12] and produced a valved conduit with the GA-fixed bovine pericardia treated with our combined anticalcification protocol, which had been proven effective in small-animal experiments [6].…”
Section: Introductionmentioning
confidence: 99%
“…We further demonstrated the GA cross-linked bovine pericardium with a combination of short-and long-chain alcohol had a superior anticalcification effect. 6 Our previous studies showed that GA and organic solvent treatment had better mechanical durability than GA treatment alone and did not cause a loss in the tensile strength, elasticity, and thermostability. 18,19 Amino groups can improve protein cross-linking and neutralize toxicity of free aldehyde groups.…”
Section: Discussionmentioning
confidence: 96%
“…11 Treatment with organic solvents, such as ethanol, octanol, and octanediol, are known to reduce the phospholipid content and prevent calcium phosphate nucleation. 6 We used a short-and long-chain alcohol combination organic solvent. Pathak et al 17 reported that bovine pericardium treated with a short-and long-chain alcohol combination shows a reduction in phospholipid content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation